2017
DOI: 10.22302/iribb.jur.mp.v85i2.257
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi famili gen putatif penyandi protease inhibitor dengan pendekatan in silico komparatif pada genom Hevea brasiliensis Muell. Arg (Identification of putative gene family encoding protease inhibitors by in silico comparative analysis in Hevea brasiliensis Muell. Arg genome)

Abstract: Protease inhibitors (PIs) are small proteins that form complexes with proteases and inhibits their proteolytic activity. Its potential application as an antimicrobial agent has been studied. Most of PIs' molecule size is around 8-22 kDa depending on their protein families.To date, on the basis of sequence homologies of inhibitor domains, PIs have been classified into 48 families in all organisms. In plant, more than 13 families of PIs have been identified but they were not widely identified in the rubber tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Metode Neighbor-Joning digunakan untuk pembuatan pohon filogenetik. Metode ini digunakan pada software MEGA XI dengan nilai bootstrap dari 1000 ulangan (Martiansyah et al, 2017). Nilai bootstrap yang rendah tidak cukup untuk keakuratan jarak antar spesies pada pohon filogenetik.…”
Section: Pohon Filogenetik Dan Jarak Genetikunclassified
“…Metode Neighbor-Joning digunakan untuk pembuatan pohon filogenetik. Metode ini digunakan pada software MEGA XI dengan nilai bootstrap dari 1000 ulangan (Martiansyah et al, 2017). Nilai bootstrap yang rendah tidak cukup untuk keakuratan jarak antar spesies pada pohon filogenetik.…”
Section: Pohon Filogenetik Dan Jarak Genetikunclassified
“…Taken together, the studies showed that the protease inhibitors were encoded by numerous genes. A comparative genome analysis between Arabidopsis thaliana and Hevea brasiliensis has been carried out to putatively identify the gene family encoding Hevea protease inhibitors (HbPIs) [16]. Further transcript quantification analyses are necessary to confirm the presence of these genes in the latex.…”
Section: Introductionmentioning
confidence: 99%